The Principle of Utmost Good Faith in Insurance Following the Decision of the Constitutional Court of the Republic of Indonesia Number 83/PUU-XXII/2024 - Evi; Tinambunan, Hezron Sabar Rotua; Jalianery, Joanita (Faculty of Law, Universitas Pekalongan, 2025)
The principle of utmost good faith is the primary foundation of insurance contracts, requiring transparency between the insurer and the insured. This principle ensures contractual fairness by requiring both parties not to conceal material facts that could affect the validity of the contract. The Constitutional Court of the Republic of Indonesia Decision Number 83/PUU-XXII/2024 introduces a new dimension to the application of this principle, particularly regarding the protection of the insured's constitutional rights and the strengthening of insurance companies' transparency obligations. This article aims to analyze the implications of the Constitutional Court's decision on the practice of implementing the principle of utmost good faith, both from a doctrinal and normative perspective. The research method used is normative legal research with a statutory and case-based approach. The results of the study indicate that the Constitutional Court's decision emphasizes the urgency of the principle of utmost good faith as a legal protection mechanism that balances the interests of insurance companies and the rights of the insured.